Application of Mine Dewatering Methods to Reduce Wastewater Pollution in The Environment: Implications for Andesite Mining - A.A Inung Arie Adnyano; Rizqi Prastowo; Muhammad Nauval Bahy; Syouma Hikmahtiar; Ahmad Said; Abdul Latif Ashadi (CV FOUNDAE, 2022)
Wastewater pollution in mining areas often occurs and becomes a problem in the surrounding groundwater aquifer system. One of the efforts to determine the distribution of wastewater pollution is to calculate the discharge and volume of wastewater. In this study, an open channel in the form of a ditch or commonly referred to as a drainage system is carried out to determine the total water discharge entering the research location, design the dimensions of the sump and design the optimal cross-sectional dimensions of the ditch to overcome the discharge of water that comes out and pollutes the environment. The method used is to make an open channel in the form of a trapezoid to be used around the andesite rock mining site which then drains the mine water to the setlingpond. Efforts to drain the water that has entered the main sump (mine dewatering system) are carried out by making wells, after which the waste water is channeled into the settling pond using a pump. From the results of the study, information was obtained that the total water discharge entering the sump was 235,175 m so that the volume of the sump made was 300 m with dimensions of top area: 20m x 10m, bottom area: 10m x 10m, with a depth of 2m for total water discharge for ditches. 0.0237 m so that the volume of the trench made is 0.228 m.